LEARNING BLOG AS AN ALTERNATIVE INSTRUCTIONAL MEDIA AT SMP NEGERI 1 NGASEM KEDIRI - Ananda, Kun Sila (Wisesa: Jurnal Pengabdian Masyarakat, 2022)
Abstract One of the problems in distance learning that was implemented during pandemic was the absence of face-to-face learning process in class between students and teacher. The same thing was experienced by teachers of the social sciences subject at SMP Negeri 1 Ngasem Kediri. It is in this position that the teacher is then required to be more creative in designing learning and facilitating students to continue to gain knowledge. One way that can be done is through improving teacher skills which is one of the goals of this community service. Improving teacher skills is carried out through workshops and training on developing learning blogs for social science teachers at SMP Negeri 1 Ngasem. Activities carried out include Focus Group Discussions (FGD) and Workshops which are held online. From the results of the implementation of community service, it was found that social science teachers at SMP Negeri 1 Ngasem were able to take part in blog development training well. In addition, teachers become motivated to create their own learning blog. Abstrak Salah satu permasalahan dalam pembelajaran jarak jauh (PJJ) yang diterapkan pada masa pandemic ini adalah ketidakhadiran guru secara langsung dalam proses belajar mengajar. Hal serupa juga dialami oleh guru rumpun ilmu sosial di SMP Negeri 1 Ngasem Kediri. Pada posisi inilah guru kemudian dituntut untuk lebih kreatif dalam merancang pembelajaran dan memfasilitasi siswa agar tetap mendapatkan ilmu pengetahuan. Salah satu cara yang bisa dilakukan adalah melalui peningkatan keterampilan guru yang menjadi salah satu tujuan pengabdian kepada masyarakat ini. Peningkatan keterampilan guru dilakukan melalui workshop dan pelatiahn pengembangan blog pembelajaran untuk guru rumpun ilmu sosial di SMP Negeri 1 Ngasem. Kegiatan yang dilaksanakan, antara lain adalah Focus Group Discussion (FGD) dan Workshop yang dilaksanakan secara daring. Dari hasil pelaksanaan pengabdian kepada masyarakat tersebut didapatkan bahwa guru rumpun ilmu sosial di SMP Negeri 1 Ngasem dapat mengikuti pelatiahn pengembangan blog dengan baik. Selain itu, guru menjadi termotivasi untuk membuat blog pembelajaran sendiri.